Physics Learning Technology for Sustainable Development Goals (SDGs): A Literature Study - Prayogi, Saiful; Verawati, Ni Nyoman Sri Putu (International Journal of Ethnoscience and Technology in Education, 2024)
The integration of technology in physics education has become increasingly important to meet the Sustainable Development Goals (SDGs), particularly in enhancing educational quality, promoting inclusivity, and fostering sustainable practices. This literature study aims to evaluate the effectiveness of various technological tools, including adaptive learning platforms, augmented reality (AR), virtual reality (VR), artificial intelligence (AI), and virtual laboratories, in improving physics education. Utilizing a systematic literature review methodology adhering to PRISMA guidelines, the study analyzed data from a comprehensive selection of peer-reviewed articles sourced from the SCOPUS database, focusing on publications from 2020 to 2024. The results indicate that these technologies significantly enhance student engagement, understanding, and critical thinking skills, thus addressing the limitations of traditional teaching methods. Adaptive learning strategies, when combined with techniques like flipped classrooms and micro-learning, effectively cater to individual student needs, promoting personalized learning experiences. AR and VR provide immersive learning environments, making complex physics concepts more accessible and engaging, while AI tools support lesson planning and problem-solving. Virtual laboratories offer hands-on experimental practice without the constraints of physical lab space. However, the study also identifies challenges such as inadequate teacher training, unequal access to technology, and the need for comprehensive professional development programs. The implications of these findings underscore the necessity of addressing these challenges to fully realize the potential of technology-enhanced education. Recommendations include developing professional development programs, ensuring equitable access to technological resources, and fostering collaborations between educational institutions, industry, and communities.